Exam Ref 70-533 : implementing Microsoft Azure infrastructure solutions - Rainey, Rick (Published with the authorization of Microsoft Corporation by Pearson Education, 2018)
Prepare for Microsoft Exam 70-533 - and demonstrate your real-world mastery of implementing infrastructure solutions using Microsoft Azure. Designed for experienced developers ready to advance their status, Exam Ref focuses on the critical-thinking and decision-making acumen needed for success at the Microsoft Specialist level.